Development of Local Wisdom-Based Media in Improving Process Practicality Elementary Social Studies Learning - Muh Usri; Azis Muslimin; Idawati I (Universitas Pendidikan Indonesia (UPI), 2023)
The development of media based on local wisdom in increasing the practicality of the elementary social studies learning process is a rare thing to do to overcome problems in the learning process. The reality found in the field is the lack of interest of students in participating in the learning process, this is the basis for developing a media in order to give birth to new innovations in a learning process in order to create active and fun learning so that students can develop abilities in understanding the material presented. taught. The purpose of this study was to develop media based on local wisdom in increasing the practicality of the elementary social studies learning process. This research is a development research using the ASSURE model (Analyze Learners; State Objectives; Select Methods, Media, and Materials; Utilize Media and Materials; Require Learner Participation; and Evaluate and Rivise). The practicality test is carried out after the development stage. The data collection technique in this study was using a questionnaire, namely a teacher response questionnaire and a student response questionnaire. Data validation was carried out by 3 validators, namely 2 expert validators in the field of social sciences and 1 practitioner validator. Practical analysis uses the results of teacher and student responses. Media is said to be practical if it is at a fairly practical level, namely at number 3 and if it is at number 4 it can be said to be very practical. Based on the results of the analysis, media based on local wisdom is stated to be quite practical,